2009
DOI: 10.1007/s10549-009-0554-3
|View full text |Cite
|
Sign up to set email alerts
|

Axillary nodal metastases from carcinoma of unknown primary (CUPAx): a systematic review of published evidence

Abstract: Axillary lymph node metastases from adenocarcinoma or poorly differentiated carcinoma of unknown primary (CUPAx) represent a rare clinical entity without consensus on its biology, management and outcome. We systematically reviewed published CUPAx series and identified 24 retrospective studies enrolling 689 patients from 1975 till 2006. CUPAx affected women at a mean age of 52 years, 66% of whom post-menopausal harbouring low-volume (N1, 48%) or high-volume (52%) nodal disease from ductal adenocarcinoma (83%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 40 publications
3
74
1
3
Order By: Relevance
“…Breast tumors commonly metastasize to this site, and this type of CUP is found almost exclusively in women. However, breast tumors were not identified in 28% of 446 women who were diagnosed with this type of CUP and underwent mastectomy and subsequent histological analysis [2,39]. The terms primary tumor and secondary tumor should also be avoided in the absence of a primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Breast tumors commonly metastasize to this site, and this type of CUP is found almost exclusively in women. However, breast tumors were not identified in 28% of 446 women who were diagnosed with this type of CUP and underwent mastectomy and subsequent histological analysis [2,39]. The terms primary tumor and secondary tumor should also be avoided in the absence of a primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that occult breast cancer with axillary metastasis should be treated in the same way as breast cancer with a comparable nodal stage is treated [6]. According to a report that analyzed 24 studies on axillary nodal metastasis from CUP, 321 of 446 patients (72%) who underwent mastectomy showed pathological signs of occult breast cancer, which suggests that mastectomy is an effective diagnostic and therapeutic modality [14]. On the contrary, other studies reported that there was no difference in the survival rates of patients, who underwent mastectomy and patients, who preserved their breasts, which suggests that mastectomy is not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies focusing on OBC also evaluated patients with histopathological identification of invasive carcinoma on the breast. A review focusing on 689 patients included in 24 retrospective series of OBC was recently reported [20]. Amongst a total of 446 patients managed with mastectomy, an occult breast primary tumour was eventually identified histologically in 321 patients (72%).…”
Section: Discussionmentioning
confidence: 99%